Flow-cytometric DNA analysis as a means for early detection of malignancy in patients with chronic ulcerative colitis. Issue 8 (August 1984) - Hammarberg, C; Rubio, C; Slezak, P; Tribukait, B; Ohman, U
Abstract : A new approach to the problem of monitoring patients with chronic ulcerative colitis is presented and discussed in connection with a case report. When annual colonoscopies are performed, biopsies are taken for histopathological examination and DNA measurements are made using flow-cytometric techniques (FCM). Using the latter approach, gross chromosomal aberrations indicating malignant transformation in a cell population may be detected. In a 46 year old man with a long history of ulcerative colitis, an area with slight mucosal dysplasia at light microscopy was accompanied by two aneuploid cells lines - that is, colonic mucosa cells with an abnormal amount of DNA in the nuclei. An operation one year later revealed a 5 X 2 mm large adenocarcinoma in the corresponding area of the colon. We suggest that flow-cytometric techniques can be used as a complement to already practised methods for monitoring the colorectal mucosa in colitic patients for the early detection of malignancy.